Chronology of an Elite Mound of the Yamnaya Culture Boldyrevo IV Burial Ground in the Orenburg Region According to Stratigraphy, Burial Rite and Radiocarbon Dating - Morgunova Nina L.; Faizullin Airat A. (Поволжская археология, 2024)
The aim of this paper is to publish new radiocarbon dating data for three complexes stratified under one mound (mound No. 1 in the Boldyrevo IV burial ground in the Western Orenburg region), which are distinguished by the unusual nature of the burial in comparison with the known, reference necropolises of the Yamnaya culture. Kurgan 1, one of the largest in the Volga region and the Southern Urals, was investigated in 2019–2020. The early horizon was represented by two small mounds above the burials of children, surrounded by ditches consisting of separate pits. Later, between the mounds for children, a collective burial of five adults took place in a huge burial chamber with a complex design, over which a large mound was built, which also covered both children’s mounds. All the main burials under the early mounds and burial 5 under the large mound represent a single cultural and epochal complex and belong to the Yamnaya culture. According to archaeological and paleo-soil data, the construction of mound 1 occurred systematically over a time interval that is approximately 200 years. Radiocarbon dating showed that the construction of the mound occurred within the calibrated interval of 3200–2600 BC years. The site, apparently, before and during the creation of the mound, was the site of sacred ceremonies and public meetings of many clans of the Yamnaya culture. The induction burial of two women took place at the top of the mound at the end of the Bronze Age.